Injuries and death of children in rollover motor vehicle crashes in the United States. Issue 1 (1st March 2003) - Rivara, F P; Cummings, P; Mock, C
Abstract : Context: There is an increased awareness of the problem of rollover crashes, but few data on children involved in rollover crashes in the United States. Objective: To determine: (1) the rates of rollover crashes involving children and the incidence of fatal injury; (2) the characteristics of crashes involving children; (3) the risk factors for children being in a rollover compared with a non-rollover crash; and (4) whether the risk of death is greater for children involved in crashes in sport utility vehicles (SUVs) or passenger cars. Design: Retrospective cohort study. Data: 1993 through 1998 crashes involving children younger than 16 years included in the Crashworthiness Data System or reported to the Fatality Analysis Reporting System. Results: During the study period, 100.4 children per 100 000 person-years were involved in a rollover crash, accounting for 10% of all children involved in crashes. The incidence of fatal injuries in rollover crashes was 3.4 per 100 000 person-years. Sixty percent of children involved in rollovers were riding in SUVs. Among vehicles carrying children and involved in a crash, the adjusted relative risk of the crash being a rollover was 11.1 (95% confidence interval (CI) 9.3 to 13.3) for SUVs compared with passenger cars. The adjusted relative risk of death was 1.8 (95% CI 1.1 to 2.8) in a rollover crash and the relative risk of injury was 2.1 (95% CI 1.1 to 3.8) compared with non-rollover crashes. However, the relative risk of death for children in SUVs which crashed was 0.4 (95% CI 0.1 to 2.5) compared with passenger cars which crashed. Conclusions: Crashes involving children in SUVs were more likely to be rollover crashes than those involving passenger cars, and rollover crashes were associated with an increased risk of death and injury. However, the overall risk of death for children in a crash was not higher for children who crashed in an SUV compared to children who crashed in a passenger vehicle. Whether children are safer overall in SUVs compared with other cars cannot be answered with the data used.